Pregnant Women's Health Education About Exclusive Breastfeeding For Babies In Aek Haruaya Village, Sub-District Portibi, North Padang Lawas Regency In 2026 - Ica Fauziah Harahap; Riska Yanti; Rina Marlina Hutasuhut (International Journal of Community Service (IJCS), 2026)
Exclusive breastfeeding is breast milk given to babies from birth for six months without adding and/or replacing it with other foods or drinks. The initial phase in the life cycle which is a critical period for nutritional management is the infant phase. In this phase, very rapid growth and development occur, requiring high nutritional needs. Malnutrition disorders that occur in the infant phase can be permanent and cannot be recovered even if subsequent nutritional needs are met. This research is an analytical survey using a cross-sectional design. This community service activity was carried out in Aek Haruaya Village, Portibi District, North Padang Lawas Regency in 2026. The target of this activity was 39 pregnant women domiciled in Aek Haruaya Village. It is hoped that after this activity, pregnant women's knowledge about Exclusive Breastfeeding will increase, thereby increasing the coverage of Exclusive Breastfeeding, especially in the Aek Haruaya Village area.